Metal-Catalyzed Isomerization of 5-Heteroatom-Substituted Isoxazoles as a New Route to 2-Halo-2H-azirines - Rostovskii, Nikolai V.; Agafonova, Anastasiya V.; Smetanin, Ilia A.; Novikov, Mikhail S.; Khlebnikov, Alexander F.; Ruvinskaya, Julia O.; Starova, Galina L. (Synthesis, 2017)
A convenient gram-scale method for the preparation of 2-halo-2H-azirine-2-carboxylic acid esters, thioesters and amides via metal-catalyzed isomerization of 5-heteroatom-substituted 4-haloisoxazoles is developed. The formation of the esters and amides is efficiently catalyzed by Rh2(Piv)4, while FeCl2·4H2O is the catalyst of choice for the synthesis of the thioesters. In addition, rhodium catalysis is successfully applied in the synthesis of azirine-2-carboxylates from non-halogenated 5-alkoxyisoxazoles.
Keywords: azirines; isoxazoles; haloheterocycles; rhodium(II) carboxylates; iron(II) chloride; catalysis; isomerization